Crosstalk Between Staphylococcus aureus and Innate Immunity: Focus on Immunometabolism - Horn, Christopher M.; Kielian, Tammy (Frontiers in Immunology, 2021)
Staphylococcus aureus (S. aureus) is a leading cause of bacterial infections globally in both healthcare and community settings. The success of this bacterium is the product of an expansive repertoire of virulence factors in combination with acquired antibiotic resistance and propensity for biofilm formation. S. aureus leverages these factors to adapt to and subvert the host immune response. With the burgeoning field of immunometabolism, it has become clear that the metabolic program of leukocytes dictates their inflammatory status and overall effectiveness in clearing an infection. The metabolic flexibility of S. aureus offers an inherent means by which the pathogen could manipulate the infection milieu to promote its survival. The exact metabolic pathways that S. aureus influences in leukocytes are not entirely understood, and more work is needed to understand how S. aureus co-opts leukocyte metabolism to gain an advantage. In this review, we discuss the current knowledge concerning how metabolic biases dictate the pro- vs. anti-inflammatory attributes of various innate immune populations, how S. aureus metabolism influences leukocyte activation, and compare this with other bacterial pathogens. A better understanding of the metabolic crosstalk between S. aureus and leukocytes may unveil novel therapeutic strategies to combat these devastating infections.